2020
DOI: 10.1063/5.0002769
|View full text |Cite
|
Sign up to set email alerts
|

Laser-heated capillary discharge plasma waveguides for electron acceleration to 8 GeV

Abstract: A plasma channel created by the combination of a capillary discharge and inverse Bremsstrahlung laser heating enabled the generation of electron bunches with energy up to 7.8 GeV in a laser-driven plasma accelerator. The capillary discharge created an initial plasma channel and was used to tune the plasma temperature, which optimized laser heating. Although optimized colder initial plasma temperatures reduced the ionization degree, subsequent ionization from the heater pulse created a fully ionized plasma on-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…At n e = 2 × 10 17 electrons/cm 3 the peak accelerating field (estimated based on the cold plasma wave-breaking limit) is 43 GV/m. A 1% variation in n e (0) translates to changes of ∼0.22 GV/m or ∼0.5%, much smaller than the variations that are typically observed in experiments [42,43] .…”
Section: Lpasmentioning
confidence: 69%
See 1 more Smart Citation
“…At n e = 2 × 10 17 electrons/cm 3 the peak accelerating field (estimated based on the cold plasma wave-breaking limit) is 43 GV/m. A 1% variation in n e (0) translates to changes of ∼0.22 GV/m or ∼0.5%, much smaller than the variations that are typically observed in experiments [42,43] .…”
Section: Lpasmentioning
confidence: 69%
“…Matched spot size variations were largest ( w m =0.2%) for the longest capillary (40 cm). We project that these quantities are not sufficient to cause the large electron beam parameter variations that are typically observed in laser-driven plasma wakefield acceleration experiments to date [42,43] . Improvements of the quality and reproducibility of particle bunches accelerated in laser-driven plasma wakefields therefore require improvements of the laser pulse parameter variations [44] .…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…Further, employing methods to increase the channel depth [47] is expected to increase the attenuation length above 1 m, leading to negligible propagation losses. Channels of this type would have an energy transmission which would equal or exceed that demonstrated by gas-filled capillary discharge waveguides [48], which, for example, have demonstrated a transmission above 80% for low-intensity pulses guided in 90 mm long channels.…”
Section: Discussionmentioning
confidence: 93%
“…A power attenuation length of L att ≈ 0.15 m has been reported for capillary discharge waveguides [18] and that for the lowest-order mode of hollow capillary waveguides [11,40] is L att ≈ 0.9 m for a 50-μmdiameter capillary. Gonsalves et al [23] have reported an energy transmission of 85% for low-intensity pulses guided in 90-mm-long laser-assisted capillary discharges, corresponding to L att ≈ 0.6 m, assuming perfect coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Many methods for guiding high-intensity laser pulses have been investigated. These include grazing-incidence guiding in capillaries [11] and many varieties of plasma channels generated by hydrodynamic expansion [12][13][14][15], capillary discharges [16][17][18], Z pinches [19,20], open-geometry discharges [21], and laser-heated capillary discharges [22,23]. To date, the most successful approaches for driving laser-plasma accelerators are capillary discharges and its laser-heated variant, which have been used to generate electron beams with energies up to 4.2 and 7.8 GeV respectively [24,25].…”
Section: Introductionmentioning
confidence: 99%